Organizational Aspects Of Family Welfare Programme In India - Chaurasia A R (Wolters Kluwer Medknow Publications, 1985)
Family welfare can be regarded as an organization in the larger distributive network of development services. In such an organization, administrative capacity plays an important role. The present study analyses the performances of Indiaâ€s National Family welfare programme in the context of its administrative efficiency and organizational capacity. By utilizing the productivity of the staff cost efficiency and expenditure per staff. This article analyses the impact of the organizational the impact of the organizational aspects of the programme on the performance of the programme.